The STUDENTS’ ABILITY TO IDENTIFY MAIN CLAUSE AND SUB CLAUSE ON REPORTED SPEECH BY FIFTH SEMESTER AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Siti Hardianti Nasir; Herlina Daddi; Ika Sastrawati (Journal of Language Testing and Assessment, 2022)
This research aimed to aimed to find out students’ ability to identify main clause and sub clause on reported speech By fifth semester At Muhammadiyah University of Makassar. This study used a descriptive quantitative research approach. The sample size was 30 students in total. Purposive sampling was utilized by the researcher. The data gathering instrument was written test.Based on the findings, the researcher found tha students’ ability to identify main clause and sub clause. Total score of the main clause test was 2.212, and the total numbers of the students were 30 while mean score of the students’ ability to identify main clause was 73.73 (good). Total score of the sub clause was 2.212, and total numbers of the students were 30 while the mean score of the students’ ability to identify sub clause was 73.73 (good) means some students were still difficult to determine them, and some students were having good comprehension about them. However this score need to be improved because this category is still low for college’s students.From the findings above, it can be concluded that students’ ability in identifying main clause and sub clause have good comprehension. However, the researcher concluded this score need to be improved.